Perkembangan Motorik Halus Pada Anak Usia Dini - Ahmad Syukri Sitorus (JURNAL RAUDHAH, 2016)
Fine motor is a movement involving certain body parts only and is carried out by small muscles as well as intricate and hand-eye coordination. Motor development of children is not only seen from the genetic, but internal and external factors. fine motor development dimensions there are three children namely movement reflexes, timing and dexterity and hand dominance. Improved fine motor skills can be done through three ways, first, learn to try and error, both mimicking and third training.